Millennials, Peacebuilding, and Popular Islamic Novels: Exploring Transformative Bridges for Interfaith Relations - Nurul Aula, Siti Khodijah; Ichwan, Moch Nur (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
This article explores the role of interfaith relations in Indonesian society, with a particular focus on their representation in contemporary Islamic novels. While various programs have been implemented to foster interfaith harmony, the role of literature in promoting such relationships has received less attention. This study highlights the incorporation of interfaith themes within contemporary Islamic novels, where romantic storylines are intertwined with Islamic teachings. Millennials and young people, who constitute a significant portion of the readership, find enjoyment in these narratives and ideologies. The inclusion of interfaith narratives in these novels serves as a countermeasure to the popular "chick lit" genre that employs vulgar language and lacks religious nuances. Employing Ervin Goffman's theory of dramaturgy, the research focuses on the works of Habibburahman El Shirazy and Asma Nadia as representative popular Indonesian Muslim novelists. The findings reveal that Islamist novels have received positive responses from millennial readers, and the elegant delivery of interfaith values contributes to peacebuilding within the context of this generation. Overall, this study emphasizes the promotion of peace and interfaith understanding through the medium of popular Islamic novels, catering to the needs and preferences of the millennial demographic.